Effectiveness of Protective Action of Coatings from Moisture Sorption into Surface Layer of Sand Moulds - Kaźnica N. (Archives of Metallurgy and Materials, 2016)
The results of investigations of the sorption process of surface layers of sand moulds covered by zirconium and zirconium - graphite alcohol coatings are presented in the paper. Investigations comprised two kinds of sand grains (silica sand and reclaimed sand) of moulding sand with furan resin. Tests were performed under conditions of a high relative air humidity 75 - 85% and a constant temperature within the range 28 – 33°C. To evaluate the effectiveness of coatings protective action from moisture penetration into surface layers of sand moulds gravimetric method of quantitavie moisture sorption and ultrasonic method were applied in measurements.